A Unique Manifestation of Postural Orthostatic Tachycardia Syndrome (POTS) Resembling Symptoms of Irritable Bowel Syndrome - Alshmandi, Mohamed; Khan, Jasim; Kiernan, Julia (Scripta Medica, 2024)
Postural orthostatic tachycardia syndrome (POTS) exhibits a broad spectrum of presentations, with severity varying from individual to individual. These diverse symptoms vary from person to person but usually presents with palpitations, dizziness, blurred vision, mental fatigue, collapse, shortness of breath and chest pain. It may also manifest with less usual presentations including abdominal symptoms that can often go misdiagnosed or undiagnosed for a long time. A case of a 29 years-old woman, who was hospitalised for evaluation of persistent abdominal discomfort accompanied by bloating and chronic episodes of watery diarrhoea is presented. Diagnosis of POTS was established. It's crucial to consider POTS in the differential diagnosis for patients displaying autonomic symptoms, including those related to the abdomen.
Keywords: Postural orthostatic tachycardia syndrome; Irritable bowel syndrome; Dizziness